Corporate Governance Scorecards : Assessing and Promoting the Implementation of Codes of Corporate Governance - International Finance Corporation (Washington, DC, 2014)
This is a supplement to second IFC's toolkit: developing Corporate Governance codes of best practice. The focus of second toolkit is the development of codes of corporate governance. This supplement focuses narrowly on how to use scorecards to measure the observance and implementation of such codes. It does not cover the full panoply of governance assessment tools. This supplement provides practical guidance and a step-by step approach on how to develop a corporate governance scorecard. It also presents different approaches to scorings based on the experience of different scorecard users in different countries. This supplement is not intended to be a full manuscript of all the available tools or assessment techniques but more a guidance on various possible uses and applications of scorecards It is, however, intended to cover most of the issues that might confront any institution, regulator, stock exchange, and so on, that has in mind to develop a scorecard and to provide some practical guidance on how to approach those issues. This supplement provides practical guidance and a step-by step approach on how to develop a corporate governance scorecard. It also presents different approaches to scorings based on the experience of different scorecard users in different countries. The supplement also shows how scorecards are adapted to local circumstances and the local corporate governance framework.